Pengembangan Ekstrak Etanol Limbah Biji Pepaya (Carica papaya L.) Sebagai Serum Antijerawat - Andi Hasrawati; Hardianti Hardianti; Adisti Qama; Muhammad Wais (Jurnal Fitofarmaka Indonesia, 2020)
Acne or commonly called acne vulgaris merupahkan abnormalities in the skin that almost everyone has experienced it. Acne is a problem of skin, neck, chest, and back that occurs in times of skin-the skin of the skin will be clogged by excessive fat deposits. Propionibacterium acnes is a gram-positive bacteria as part of normal flora and fauna. Papaya seeds are agricultural waste that has antibacterial activity against the bacteria Propionibacterium acnes with a very low cost. One of the proper acts for acne problem is by using serum. Serum has a very fast absorptive effect to penetrate the inner skin without the effects of sticky effects on the skin. By knowing that the bacteria Propionibacterium acnes can cause acne that can attack various circles and know the benefits of papaya seeds that inhibit the growth of acne-causing bacteria, it is necessary to formulate papaya seed estrak as antijerawat, so this process formulates the serum preparation of papaya seed estrak which can as pen prevent the growth of acne-causing bacteria. The research method that will be done is the initial processing of the sample by extraction and then proceed with formulation of the preparation. After that, the evaluation of serum preparation and antibacterial activity test are available on the preparation.